Stability of the null solution of the equation ẋ(t) = -a(t)x(t) + b(t)x([t]) - Marconato, Suzinei A. S. [UNESP]; Bená, Maria A. [UNESP] (My University, 2010)
The asymptotic stability of the null solution of the equation ẋ(t) = -a(t)x(t)+b(t)x([t]) with argument [t], where [t] designates the greatest integer function, is studied by means of dichotomic maps. © 2010 Academic Publications.
Keywords: Dichotomic maps; Piecewise constant argument; Stability